Correlation between placental bacterial culture results and histological chorioamnionitis: a prospective study on 376 placentas. Issue 3 (25th December 2012) - Queiros da Mota, Vanessa; Prodhom, Guy; Yan, Pu; Hohlfheld, Patrick; Greub, Gilbert; Rouleau, Caroline
Abstract : Objective: To study the correlation between the bacteriological and histopathological findings in placentas from women with suspected or proven chorioamnionitis (CA). Methods: Over a 1-year period, 376 placentas were prospectively collected and processed for bacteriological and pathological studies in cases of confirmed or suspected maternal or neonatal infection. Results: Histological CA was diagnosed in 26.9% of placentas (101/376), and 27.7% (28/101) of these placentas had positive bacteriological cultures. A monomicrobial culture, mainly represented by Gram-positive cocci and Gram-negative bacilli, was identified in 27% of the positive bacterial cultures. The proportion of positive cultures was higher (p=0.03) when CA was associated with funisitis, as compared with placental samples with early CA. In placentas without histological CA, bacteriological cultures were mostly negative (230/275), although pathogenic bacteria were identified in 16.3% of them (45/275). Conclusions: The histological and bacteriological results were concordant in about 70% of the examined placentas, with 61.1% negative cases (CA absent and negative bacterial cultures), and only 7.4% placentas with positive histological and bacteriological results. Discordant results (positive histology with negative bacteriology) were obtained in placentas with early CA documented by histology although possibly in relation with antibiotic prophylaxis and the presence of fastidious bacteria. Conversely, negative histology with positive bacteriology could be explained by the presence of an early-stage bacterial infection that has not yet led to detectable microscopic lesions.